Jacob Mincer Award (Journal of Labor Economics, 2024)
Society, and the Society of Labor Economists.For more than three decades, Janet has pioneered research on the role of education, family background, social transfer programs, access to health care, and environmental factors in shaping the health and well-being of children and their outcomes as adults.She was a prime mover in making the study of the fetal period and child development an essential concern of labor economics.This pioneering work had a major influence on other fields, including the economics of education, health economics, public economics, and environmental economics.In the early 1990s, Janet started a research agenda on the effectiveness of early childhood